Bibliometric Analysis Using VOSviewer to Measure Research Developments on Sharia Banking - Rivian Anda Sari (Rangkiang: Journal of Islamic Economics and Business, 2023)
This research aims to carry out bibliometric analysis using VOSviewer to measure the development of research on Sharia Banking. This research uses descriptive quantitative methodology in Measurement to examine Islamic Banking Research. This research on Sharia Banking starts from 1970 to 2022, according to Dimensions' search with the keyword Sharia Banking. The results of this search contained 2,607 research publications with 683 Authors, 419 Clusters, 397 Links, and a Total link strength of 403. The results of the research were analyzed descriptively, inputted, and analyzed using VOSviewer and by reviewing literature reviews to determine the visual form of measuring developments on topics surrounding Sharia Banking. The research results show that publications increase significantly every year. Based on measurements from the use of VOSviewer, research regarding the development of Sharia Banking has 885 citations and 0.34 Citations (mean). The main contribution of this research is to determine the expansion of research on Sharia Banking and themes that are rarely studied about Sharia Banking.